2020
DOI: 10.1097/md.0000000000021985
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric gastritis and its impact on hematologic parameters

Abstract: Non-invasive biomarkers, such as neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios, may predict inflammation in various disorders, including gastritis, according to recent data. Nevertheless, various studies reported an association between Helicobacter pylori ( H pylori ) and immune thrombocytopenia in both adults and pediatric patients. The objective of our study was to evaluate the impact of pediatric gastritis, caused or not by H pylori … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…Although abdominal pain, nausea, vomiting, anorexia, weight loss, or heartburn are commonly encountered in children with H. pylori infection, the clinical picture remains unspecific[ 2 ]. Recent studies have also noted several extra-digestive manifestations such as thrombocytopenia, anemia, eosinophilic esophagitis, or otitis media that might be related to the presence of H. pylori in children[ 3 - 5 ]. Nevertheless, taking into account the difficulties related to performing endoscopic studies in children and therefore the scarcity of information in this age group, a precise cause-effect relationship between these manifestations and H. pylori has been difficult to establish.…”
Section: Introductionmentioning
confidence: 99%
“…Although abdominal pain, nausea, vomiting, anorexia, weight loss, or heartburn are commonly encountered in children with H. pylori infection, the clinical picture remains unspecific[ 2 ]. Recent studies have also noted several extra-digestive manifestations such as thrombocytopenia, anemia, eosinophilic esophagitis, or otitis media that might be related to the presence of H. pylori in children[ 3 - 5 ]. Nevertheless, taking into account the difficulties related to performing endoscopic studies in children and therefore the scarcity of information in this age group, a precise cause-effect relationship between these manifestations and H. pylori has been difficult to establish.…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiologic studies have reported a decreasing prevalence of pediatric H. pylori infection pointing out a significant difference between 25.6% in 2005 and 12.8% in 2017 [ 14 ]. Nevertheless, wide variations were reported among different populations in terms of prevalence mostly depending on the socio-economic status [ 7 , 8 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: New Insights On Pediatric H Pylori Infectionmentioning
confidence: 99%
“…Nevertheless, the symptoms in children with H. pylori infection remain unspecific including abdominal pain, nausea, vomiting, heartburn [ 21 , 23 ], and thus the most recent recommendation of the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) and the North American Society for Paediatric Gastroenterology, Hepatology and Nutrition (NASPGHAN) is to perform the necessary investigation for identifying the underlying cause of the symptoms and not only for assessing the presence of this infection [ 24 ]. A wide spectrum of extra-digestive conditions were proven to be associated to this infection, among which cardiovascular diseases, stroke, anemia, idiopathic thrombocytopenic purpura, eczema, rosacea, chronic hives, diabetes, thyroid disease or Alzheimer’s disease, which might be explained by the systemic inflammatory status identified even in pediatric patients diagnosed with H. pylori -positive gastritis [ 7 , 8 ]. Taking into account the severity of these aforementioned conditions and their long-life chronic pattern, the assessment of H. pylori related systemic inflammation should be a main goal in patients with this infection.…”
Section: New Insights On Pediatric H Pylori Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8 , 16 , 17 ] Moreover, red blood cell distribution width is another CBC parameter, whose utility was recently proved in patients with stroke. [ 18 ] Both NLR and PLR are simple, noninvasive markers, computed based on a routine CBC count and their utility has been proven in multiple medical fields, such as gastroenterology, [ 19 , 20 ] cardiology, [ 21 ] and oncology, [ 22 ] their elevated levels being underlined as both diagnostic and prognostic markers not only in the setting of sepsis, [ 23 ] but also in a wide-spectrum of pathologies. Moreover, baseline NLR level seems to be useful in predicting the clinical outcome of both ischemic and hemorrhagic stroke.…”
Section: Introductionmentioning
confidence: 99%